2017
DOI: 10.15252/embj.201695699
|View full text |Cite
|
Sign up to set email alerts
|

The linear ubiquitin chain assembly complex regulates TRAIL‐induced gene activation and cell death

Abstract: The linear ubiquitin chain assembly complex (LUBAC) is the only known E3 ubiquitin ligase which catalyses the generation of linear ubiquitin linkages de novo. LUBAC is a crucial component of various immune receptor signalling pathways. Here, we show that LUBAC forms part of the TRAIL‐R‐associated complex I as well as of the cytoplasmic TRAIL‐induced complex II. In both of these complexes, HOIP limits caspase‐8 activity and, consequently, apoptosis whilst being itself cleaved in a caspase‐8‐dependent manner. Ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(110 citation statements)
references
References 97 publications
3
107
0
Order By: Relevance
“…Interestingly, the nonenzymatic activity of caspase‐8 is essential for the formation of the complex because catalytically inactive caspase‐8 was able to restore TRAIL‐induced nonapoptotic signaling in caspase‐8 knockout cells. This complex was further confirmed by work from the Walczak group showing that this complex also contained TRAF2, c‐IAP1/2, and LUBAC . Surprisingly, this study also demonstrated that this complex is formed at the plasma membrane and that the LUBAC complex is a critical determinant of cell fate by restricting caspase‐8 activation through ubiquitination while activating the NF‐κB pathway.…”
Section: Unknown Factors In Disc Formationsupporting
confidence: 62%
“…Interestingly, the nonenzymatic activity of caspase‐8 is essential for the formation of the complex because catalytically inactive caspase‐8 was able to restore TRAIL‐induced nonapoptotic signaling in caspase‐8 knockout cells. This complex was further confirmed by work from the Walczak group showing that this complex also contained TRAF2, c‐IAP1/2, and LUBAC . Surprisingly, this study also demonstrated that this complex is formed at the plasma membrane and that the LUBAC complex is a critical determinant of cell fate by restricting caspase‐8 activation through ubiquitination while activating the NF‐κB pathway.…”
Section: Unknown Factors In Disc Formationsupporting
confidence: 62%
“…Since the linear ubiquitin chain assembly complex (LUBAC) plays a role in preventing cell-death-inducing complex formation in various cell types including hepatocytes (Lafont et al., 2017, Shimizu et al., 2017), it was considered a candidate signaling event. Indeed, LUBAC components HOIP, HOIL-1, and SHARPIN, as well as the inhibitor of apoptosis proteins (IAP) cIAP1, cIAP2, and XIAP, known to negatively regulate formation of the ripoptosome (Tenev et al., 2011), were transiently reduced 15 to 30 min post-doxorubicin treatment of U2OS cells (Figure 6H).…”
Section: Resultsmentioning
confidence: 99%
“…177). Recent studies indicate that RIPK1 (REFS 178,179) and LUBAC 179 can be directly recruited to membrane-bound TRAILR, suggesting that NF-κB activation can occur at the plasma membrane. Understanding the signalling circuits that are activated downstream of TRAILR is of special interest, as several TRAILR agonists have been evaluated as putative cancer therapeutics with limited clinical success (reviewed in REF.…”
Section: Cell Death Regulation By Ubiquitin Ligasesmentioning
confidence: 99%
“…The finding that TRAILR can induce migratory 180 and inflammatory responses that promote tumorigenesis 181 sheds light on the complex signalling circuits that respond to TRAIL. Therefore, fine tuning of LUBAC-mediated NF-κB activation may constitute one step to improve therapeutic effects of TRAILR agonists 179 and possible pathways that have been associated with deregulated LUBAC components.…”
Section: Cell Death Regulation By Ubiquitin Ligasesmentioning
confidence: 99%
See 1 more Smart Citation